682 Gender equity in editorial boards of medline indexed occupational safety & health journals. (24th April 2018) - Roy, Priyanka; Bhaumik, Soumyadeep
Abstract : Introduction: Gender bias in science is a global issue. Being an editor in a journal is considered to be representation of an individual's reputation and leadership. While gender disparity in editorial board of journals in several specialities, has been studied, but not in Occupational Safety and Health (OSH). Methods: MEDLINE indexed journals were searched in the NLM, USA Catalogue with a search strategy. The list of journals retrieved were reviewed to access whether they were in the domain of OSH. Information pertaining to editors and their roles was obtained from journal websites in June 2017. At this phase, journals which had no editorial list or did not have full names of editors in their websites were excluded. Any individual whose role which was not designated as editor was excluded from the analyses. Gender was determined by multiple methodologies: inspection of names, gender- specific description, photographs in journal or institutional web pages. All data was validated independently by the two authors and differences sorted by consensus. Since the study used data available in public domain and no human participants were involved it did not require ethics committee approval. Results: 22 journals were retrieved from the NLM catalogue and 16 of them were finally included with a total of 185 editors. Gender could not be determined by for 11 (5.94%) editors and there were 56 female (30.27%) editors and 118 male (63.78%) editors. 3 out of 16 (18.75%) Editor-in-Chief, 2 out of 8 (25%) Managing editors and 39 out of 101 (38.61%) Associate editors were female. Discussion: This is the first study providing data on gender diversity in editorial boards of OSH journals and shows significant gender inequity. Qualitative research to understand the enablers and barriers for women to become editors in OSH journals is warranted.